Role of local infiltration of tramadol vs. Bupivacain in postoperative laproscopic cholecystectomy pain management - Naheed Akhtar, Raja Muhammad Ijaz, Saman Naz, Irum Shahzadi,Talat Shahzad, Nadir Saifullah Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare local infiltration of Tramadol vs. Bupivacain in postoperative cholecystectomy in terms of mean pain score. Study Design. Randomized controlled trial. Place and Duration of Study: Department of Surgery, CMH, Muzaffarabad, Azad Kashmir from December 2018 to December 2019. Methodology: Total of 100 patients with 50 in each group. Cholecystectomy done with wound infiltration using Tramadol (T) in group A while Bupivacain (B) in group B at time of skin closure. Postoperative pain assessment was done by using visual analogue score (0-10) a 12 hours. Results: One hundred patients with mean age of 46.93±10.23 years were studied and male to female ratio was almost 1:2.5. The mean pain score at postoperative day one at 12 hours was recorded as (VAS 3.5±1.787) in group A (Tramadol) while mean pain score recorded as (VAS 6.0±1.195) in group B (Bupivacain).The p value was found significant <0.05. Conclusion: Our study concluded that tramadol can be used as local infiltrate for better postoperative analgesia.